Quantized fixed-time fault-tolerant attitude control for hypersonic reentry vehicles - Wu, Tiancai; Wang, Honglun; Yu, Yue; Liu, Yiheng; Wu, Jianfa (Applied Mathematical Modelling, 2021)
A quantized fixed-time fault-tolerant attitude control problem for hypersonic reentry vehicles is considered from the perspective of practical engineering. Taking into account the limited time available for recovery from a fault scenario, fixed-time extended state observers are used to simultaneously compensate for the negative effect of unknown time-varying actuator faults, uncertainties, and external disturbances. In contrast to the existing control schemes, which neglect the signal quantization transmission process and limited communication capacity, the hysteresis quantization mechanism is considered. Based on this, a fixed-time fault-tolerant control scheme is developed to ensure the fixed time convergence of all the tracking errors even in cases involving actuator faults. The stability and convergence are proven by performing a theoretical analysis. The simulation results validate the superiority and robustness of the proposed control scheme.